Innovative, Marketing and Supportive Capability Impacts Towards Logistics Performance - Mohd Fathi Mohamad; Zulkifli M Udin; Kamal Imran Sharif (International Journal of Supply Chain Management, 2018)
Logistics function as an important role in business operation. Due to the increasing competition in this industry, organization should make sure the business logistics is efficient and effective. In achieving the increase in performance and indirectly increase the profit of an organization, logistics is an important element that need be taken into consideration seriously. This paper investigates the effect of innovative, marketing and supportive capability towards logistics performance. the study has been conducted in towards the SME organization in area of Putrajaya. 117 respondents from SMEs were collected to identify the relationship of innovative, marketing and supportive capability towards the logistics performance. Hence, factor analysis was done includes the correlation and regression analysis to examine relationship that exists. The findings identify that that innovative, marketing and supportive capability that contribute to logistics performance. Index Terms: Innovative, Marketing, Supportive, Logistics Performance